Entropy generation in a micropolar fluid flow through an inclined channel - D. Srinivasacharya; K. Hima Bindu (Alexandria Engineering Journal, 2016)
In this paper the entropy generation is studied due to micropolar fluid flow through an inclined channel of parallel plates with constant pressure gradient. The lower plate is maintained at constant temperature and upper plate at a constant heat flux. The governing equations are solved by applying the spectral quasilinearization method. The velocity, microrotation and temperature profiles are obtained numerically and are used to calculate the entropy generation number. The influence of pertinent parameters on velocity, microrotation, temperature, entropy generation and Bejan number is discussed with the help of graphs. The results reveal that the entropy generation number increases with the increase in Brinkman number and angle of inclination. Further, it is observed that the increase in coupling number, Prandtl number and Reynolds number reduces the entropy generation number.